Bridging gaps, building futures: Deciphering the economic impacts of transport infrastructure and its investment in a global context - Ng, Bryan Yanxun (2024)
This study investigates the relationship between transportation infrastructure and economic growth across 48 countries, which included 33 developed countries and 15 developing countries. Transportation infrastructure is separated specifically into different types of transportation, such as road, railway, water, and air transport. Panel data analysis was conducted by employing Full-Modified Ordinary Least Square (FMOLS) and Dynamic Ordinary Least Square (DOLS) models to determine which transportation infrastructure influences economic growth within these diverse contexts. In addition, this study also includes current data on transportation infrastructure investment as a key variable for the analysis. The results show that there is a positive relationship between transportation infrastructure across developed and developing countries. Specifically, different impacts of different transportation modes on economic growth, shedding light on their respective contributions to particular countries’ RGDP. Furthermore, this study also reveals the importance of transportation infrastructure investment as a crucial promoter of economic development. This research offers important insight for researchers and policymakers who wish to maximize transportation infrastructure investment to promote sustainable economic growth as it conducted an in-depth analysis that covers both developed and developing countries. The results of this study have strategic consequences for the allocation of resources and strategic planning in the field of transportation infrastructure development. They also provide alternatives for improving economic performance and advancing equitable growth internationally. Keywords: Transportation infrastructure (road, railway, air, and water), transportation infrastructure investment, RGDP, developing countries, developed countries, panel data analysis, FMOLS, DOLS, economic growth